A Metamodel for Agile Requirements Engineering - Eva-Maria Schön and Jorge Sedeno and Manuel Mejias and Jörg Thomaschewski and Mario Jose Escalona (Journal of Computer and Communications, 2019)
Value delivery is becoming an important asset for an organization due to increasing competition in industry. Therefore, companies apply Agile Software Development (ASD) to be more competitive and reduce time to market. Using ASD for the development of systems implies that established approaches of Requirements Engineering (RE) undergo some changes in order to be more flexible to changing requirements. To this end, the field of agile RE is emergent and different process models for agile RE have arisen. The aim of this paper is to build an abstract layer about the variety of existing process models by means of a metamodel for agile RE. It has been created in several iterations and relies on the evaluation of related process models. Furthermore, we have derived process models for agile RE in industry by presenting instances of the metamodel in two different cases: one is based on Scrum whereas the other is based on Kanban. This paper contributes to the software development body of knowledge by delivering a metamodel for agile RE that supports researchers and practitioners modeling and improving their own process models. We can conclude that the agile RE metamodel is highly relevant for the industry as well as for the research community, since we have derived it following empirical research in the field of ASD.